2022
DOI: 10.1097/xcs.0000000000000058
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Accuracy of ICD-9 vs ICD-10 Codes for Acute Appendicitis

Abstract: BACKGROUND ICD codes are used to identify patients with appendicitis and to classify disease severity for reimbursement and research purposes. We sought to compare the accuracy of ICD-9 vs ICD-10 codes in classifying appendicitis as uncomplicated vs complicated (defined as perforated, necrotic, or abscess) compared with the clinical gold standard: surgeon characterization of the appendix in the operative report. STUDY DESIGN This is a retrospective revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…We also found that 57% of participants did not have any glaucoma severity staging specified, highlighting a large gap in the utilization of ICD coding for documenting and monitoring glaucoma disease severity. Given the inconsistency of results in prior literature regarding the use and accuracy of diagnosis codes, 12–15 our data suggest the underutilization of ICD codes with specified severity staging is present on a national scale, which poses a challenge when analyzing patterns of disease progression and identifying disparities among patients. When used correctly, diagnosis coding provides the opportunity to conduct population health surveillance regarding diagnosis and treatment patterns 35,36 .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We also found that 57% of participants did not have any glaucoma severity staging specified, highlighting a large gap in the utilization of ICD coding for documenting and monitoring glaucoma disease severity. Given the inconsistency of results in prior literature regarding the use and accuracy of diagnosis codes, 12–15 our data suggest the underutilization of ICD codes with specified severity staging is present on a national scale, which poses a challenge when analyzing patterns of disease progression and identifying disparities among patients. When used correctly, diagnosis coding provides the opportunity to conduct population health surveillance regarding diagnosis and treatment patterns 35,36 .…”
Section: Discussionmentioning
confidence: 83%
“…However, there has been inconsistent use and accuracy of International Classification of Disease (ICD) coding in prior studies. [12][13][14][15] Thus, even this measure requires validation in a new dataset, such as the All of Us database.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Decrease in PPV for appendicitis when the histopathology report versus the operative report was used was also seen in an American validation study of ICD-10 codes. 15 The choice of either of these two gold standards can be advocated for. The histopathology report is an excellent and rather objective gold standard if the actual and final diagnosis of the patient is sought.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the classification of perforated and non-perforated appendicitis in ICD-9 has a higher sensitivity and more accurately agrees with the surgical description of disease compared to ICD-10. 20 We opted to use the most recent years of data that are classified using ICD-9 to ensure clinical accuracy of disease severity for acute appendicitis as much as possible.…”
Section: Discussionmentioning
confidence: 99%